Étude de recherche les modèles de punitions dans la communauté bobo de Bobo-Dioulasso - Bationo, Bouma Fernand (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
Punishment, i.e. subjecting someone to a penalty in expiation for a fault, can be constructive or destructive for the person sentenced. Faced with the current crisis in educational systems, does punishment not aggravate violence? This is the question to which this report seeks to provide some answers. To this end, the author develops his thinking in three points. The first is a practical approach to the intelligibility of present-day reality, i.e. understanding how the behavior of today's teenagers came to be. The second part seeks to understand the customs and institutions designed and implemented by certain Burkinabe societies over the centuries to correct adolescents. Finally, the third part makes proposals for the education and correction of adolescents, with a view to making them true citizens, aware of their role in building a prosperous nation that contributes to the construction of the universal.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Communities; Bobo-Dioulasso